Impact of Integrated Farming Systems on Socio- Economic Status of Farmers - Rathod, M K; Raut, Sonali (Journal of Agricultural Extension Management, 2019)
The present study was conducted in Wardha district of Vidarbha region in Maharashtra to study the impact of integrated farming system on socioeconomic status of farm families. The farmers who had adopted different farming systems in addition to agriculture were purposively selected from 12 villages and personally interviewed. Data was collected regarding the impact of farming systems on socio-economic status of farmers, before and after adoption of the farming system. Almost all indicators of SES were found increased in their levels after adoption of the fanning system. The results revealed that overall socio-economic status improved after adoption of integrated farming system.